Determining return levels of extreme daily precipitation, reservoir inflow, and dry spells - Milojevic, Tatjana; Blanchet, Juliette; Lehning, Michael (Frontiers in Water, 2023)
Climate change impacts in the Swiss Alps have been seen through changes in the hydrologic regime. In addition, extreme rainfall events are expected to intensify and more severe and long-lasting droughts are expected to occur in the future. Changes in the hydrologic system can have unexpected socioeconomic impacts that can affect hydropower production optimization. As a result, understanding the potential risks of extreme events is of interest to the industry. Return level calculations are a widely used approach in estimating such risks. As the changes are not expected to be felt homogeneously, localized site assessment is important. However, for sites with relatively small datasets, selecting an applicable method for return level calculations is not straightforward. This study focuses on the application of traditional univariate extreme value approaches (Generalized Extreme Value and Generalized Pareto) as well as two more recent approaches (extended Generalized Pareto and Metastatistical Extreme Value distributions), that are specifically suited for application to small datasets. These methods are used to calculate return levels of extreme precipitation at six Alpine stations and high reservoir inflow events for a hydropower reservoir. In addition, return levels of meteorological drought and low inflow periods (dry spells) are determined using a non-parametric approach. Return levels for return periods of 10- and 20- years were calculated using 10-, 20-, and 40- years of data for each method. The results show that even shorter timeseries can give similar return levels as longer timeseries for most methods. However, the GEV has greater sensitivity to sparse data and tended to give lower estimates for precipitation return levels. The MEV is only to be preferred over GPD if the underlying distribution fits the data well. The result is used to assemble a profile of 10- and 20-year return levels estimated with various statistical approaches, for extreme high precipitation/inflow and low precipitation/inflow events. The findings of the study may be helpful to researchers and practitioners alike in deciding which statistical approach to use to assess local extreme precipitation and inflow risks to individual reservoirs.